The Influence of an Encyclopedia-Based Case Study Model on Students’ Critical Thinking and Collaboration Skills in Geography Learning in the Society 5.0 Era - Erman Syarif; Badrizal Al Hazar; Dermawan Dermawan (Universitas Negeri Gorontalo, 2026)
This study aims to analyze the effect of implementing an encyclopedia-based case study learning model on students’ critical thinking and collaboration skills in geography learning within the Society 5.0 era. Although contemporary educational demands require geography learning models that strengthen these competencies, classroom practices remain largely dominated by conventional approaches that do not optimally support their development. Geography education plays a strategic role in responding to environmental and social challenges, highlighting the need for innovative and contextual learning models. This study employed a quasi-experimental method using a pretest–posttest control group design. The participants consisted of 76 senior high school students, divided into an experimental class (n = 38) and a control class (n = 38). The experimental group implemented the encyclopedia-based case study model, while the control group received conventional instruction. Data were collected using a critical thinking skills test and a 45-item Likert-scale collaboration questionnaire. Data analysis was conducted using ANCOVA, with pretest scores treated as covariates, after meeting assumptions of normality, homogeneity of variance, and homogeneity of regression slopes. The results indicate that, after controlling for students’ initial abilities, there were significant differences between the experimental and control groups in critical thinking skills (p 0.05; ηp² = 0.302) and collaboration skills (p 0.05). These findings demonstrate that the encyclopedia-based case study learning model is effective in enhancing students’ higher-order thinking and collaboration skills and is highly relevant for implementation in geography education in the Society 5.0 era.